Thymus Functionality Needs More Than a Few TECs - Bhalla, Pratibha; Su, Dong-Ming; van Oers, Nicolai S. C. (Frontiers in Immunology, 2022)
The thymus, a primary lymphoid organ, produces the T cells of the immune system. Originating from the 3rd pharyngeal pouch during embryogenesis, this organ functions throughout life. Yet, thymopoiesis can be transiently or permanently damaged contingent on the types of systemic stresses encountered. The thymus also undergoes a functional decline during aging, resulting in a progressive reduction in naïve T cell output. This atrophy is evidenced by a deteriorating thymic microenvironment, including, but not limited, epithelial-to-mesenchymal transitions, fibrosis and adipogenesis. An exploration of cellular changes in the thymus at various stages of life, including mouse models of in-born errors of immunity and with single cell RNA sequencing, is revealing an expanding number of distinct cell types influencing thymus functions. The thymus microenvironment, established through interactions between immature and mature thymocytes with thymus epithelial cells (TEC), is well known. Less well appreciated are the contributions of neural crest cell-derived mesenchymal cells, endothelial cells, diverse hematopoietic cell populations, adipocytes, and fibroblasts in the thymic microenvironment. In the current review, we will explore the contributions of the many stromal cell types participating in the formation, expansion, and contraction of the thymus under normal and pathophysiological processes. Such information will better inform approaches for restoring thymus functionality, including thymus organoid technologies, beneficial when an individuals’ own tissue is congenitally, clinically, or accidentally rendered non-functional.